Redes de atenção à saúde : concepções e ações de nutricionistas em região do interior paulista - Rossi, Gabriela Perussi Carizani (2016)
The Care Networks Health to constitute an innovation in the organization of actions and health services, with the formation of regionalized and hierarchical network with different technological densities. These are formed from different health care points, in order to produce a positive impact on health indicators of the population. The implementation of these networks suggests an improvement of the process of realization of the Unified Health System (UHS), and also the prevalence of multiple technical interventions, articulated by the interaction of agents from different professional areas. In order to strengthen the further network, the nutritionist insertion is indispensable in the multidisciplinary team, promoting health and preventing the occurrence of new cases of diseases related to food and nutrition, agile, economical, sustainable and efficient manner. This study sought to understand the role of the nutritionist in the Health Care Networks in the São Paulo region. The population was composed of 14 professionals working nutritionists in the Health Care Networks of the 24 municipalities members of the DRS III – Araraquara/SP. The tool used for data collection in the first stage of the study, was the e-mail, via Google Drive, a Google application package, containing identification data and semi-structured questions. These data were interpreted and analyzed quantitatively. In the second stage of the research, an interview with open questions directed to the theme and the data were analyzed qualitatively and performed using the content analysis technique, taking into account the theoretical and methodological framework. The results showed that the number of nutritionists in the health services is inadequate, that the formation of these dedicated professionals for activities in the UHS is deficient and that nutritionists have a superficial knowledge about the thematic networks. In addition, the results presented show that nutritionists have some difficulties in developing its work in the Health Care Network. However, it became clear that the professional nutritionist presents a range of possibilities of action in the health service and a facility in interdisciplinary work, whose skill is essential to work in public health.